Evasion Restriction of Customs Payments in the Field of Customs Affairs - Gazinurovna, Khayrullina Rezeda; Abdulkhakovna, Shakirova Albina; Makhiyanovna, Aglyamova Gulnaz; Nakimovich, Khamitov Radik; Anvarovna, Kharisova Elvira (International Journal of Criminology and Sociology, 2022)
The main aim of the study is to analyze the basic problem of evading customs payments, which entails serious financial losses for the state budget. The article seeks to discuss the problematic issues of criminal liability for evading payment of customs duties levied on an organization or an individual, as a type of customs crime. Ways of legislative improvement of criminal law norms and aimed at combating crimes in the field of customs regulation is particular, with evasion of customs duties levied on organizations or individuals at the present stage, are proposed. The article provides an analysis of the criminal law on evasion of customs payments and smuggling, and shows a method for distinguishing related offenses using the example of evasion of customs payments and smuggling. The authors give for us a comparative analysis of the criminal law of the Russian Federation, providing for liability for smuggling and evasion of customs payments, and give the criminal legal qualification of these illegal acts. The characteristics of the elements of smuggling and tax evasion fees charged to the organization or individual are given. Based on the study, the authors draw conclusions about the development and improvement of legislation on tax evasion.